The Role of Autophagy in Mammalian Development: Cell Makeover Rather than Cell Death - Cecconi, Francesco; Levine, Beth (Developmental cell, 2008)
Autophagy is important for the degradation of bulk cytoplasm, long-lived proteins, and entire organelles. In lower eukaryotes, autophagy functions as a cell death mechanism or as a stress response during development. However, autophagy's significance in vertebrate development, and the role (if any) of vertebrate-specific factors in its regulation, remains unexplained. Through careful analysis of the current autophagy gene mutant mouse models, we propose that in mammals, autophagy may be involved in specific cytosolic rearrangements needed for proliferation, death, and differentiation during embryogenesis and postnatal development. Thus, autophagy is a process of cytosolic “renovation,” crucial in cell fate decisions.